Electronic commerce: A managerial and social networks perspective - Efraim, Turban (Springer, 2015)
Throughout the book, theoretical foundations necessary for understanding Electronic Commerce (EC) are presented, ranging from consumer behavior to the economic theory of competition. Furthermore, this book presents the most current topics relating to EC as described by a diversified team of experts in a variety of fields, including a senior vice president of an e-commerce-related company. The authors provide website resources, numerous exercises, and extensive references to supplement the theoretical presentations. At the end of each chapter, a list of online resources with links to the websites is also provided.